Reuso de água cinza residencial: um estudo de caso - Leite, Bruno de Oliveira (Universidade Federal do Tocantins, 2024)
Gray water reuse in households emerges as a crucial strategy to address the challenges of water scarcity and promote sustainable water resource management. This study aims to analyze the benefits, challenges, and practical considerations related to gray water reuse in households, aiming to provide valuable insights to promote its widespread adoption as part of a holistic and sustainable approach to water resource management. To achieve this goal, a literature review was conducted, addressing topics such as water quality, effectiveness of treatment systems, legal and socioeconomic aspects of gray water reuse. Additionally, case studies and practical examples of successful implementation of gray water reuse in different residential contexts around the world were analyzed. Water scarcity represents one of the major challenges of the 21st century, affecting millions of people worldwide and requiring urgent and effective measures to ensure equitable access to water. Gray water reuse emerges as a viable and sustainable solution to mitigate the effects of water scarcity, allowing the utilization of an alternative water source for non-potable uses such as garden irrigation, toilet flushing, and outdoor cleaning. However, its implementation faces a range of challenges, including concerns about water quality, installation and maintenance costs of treatment systems, and regulatory and cultural issues. The methodology used in this study involved a systematic literature review, with an emphasis on scientific studies, technical reports, and government documents related to gray water reuse in households. Additionally, case studies and practical examples of gray water reuse implementation in an residential contexts were analyzed, providing insights into best practices and lessons learned. Through this approach, the main benefits of gray water reuse, such as reduction of potable water consumption, cost savings, and mitigation of environmental impact, as well as the challenges and obstacles to be overcome for its widespread adoption, were identified. In summary, this study highlights the importance of gray water reuse as an essential strategy to promote sustainable water resource management in households, providing practical recommendations for its effective and sustainable implementation in different contexts.